The RAH-66 Comanche Helicopter - Linden, Arthur W. (American Institute of Aeronautics & Astronautics, 2022)
On December 5, 2003, Lt. Gen Richard A. Cody, Army Deputy Chief of Staff and an experienced aviator, flew the Comanche. According to the January 2004 issue of National Defense he ""...gave the aircraft a stellar review. ...Cody said that the Comanche had 'exceeded his expectations' and was particularly impressed by the rotor system, engine response and control. Cody also reportedly said the aircraft was 'easy to fly' and should be put into the hands of soldier.